How ancient Europeans saw the world [ vision, patterns, and the shaping of the mind in prehistoric times - Wells, Peter S. (Princeton University Press, 2012)
The people who inhabited Europe during the two millennia before the Roman conquests had established urban centers, large-scale production of goods such as pottery and iron tools, a money economy, and more. This title argues the visual world of these late prehistoric communities was different from those of ancient Rome's literate civilization